2016
DOI: 10.1111/dmcn.13282
|View full text |Cite
|
Sign up to set email alerts
|

Participation restriction in childhood phenotype of myotonic dystrophy type 1: a systematic retrospective chart review

Abstract: This study showed that patients with the childhood phenotype present a guarded prognosis regarding long-term social participation. These participation restrictions could be related to behavioural, cognitive, and social stigma problems in childhood. This study illustrates the absolute necessity to pursue an interdisciplinary follow-up of these patients when they are reaching adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
1
12
1
1
Order By: Relevance
“…Eriksson et al found that 62% of their population had a predicted need for help to live independently in the community. This is lower than that reported in the retrospective study of Gagnon et al where 91% of participants needed help to accomplish house‐related tasks independently . These diverging results could be related again to the concept of apathy, where participants are able to perform an activity in a standardized situation, but will not pursue this activity at home because of lack of interest or will.…”
contrasting
confidence: 61%
See 1 more Smart Citation
“…Eriksson et al found that 62% of their population had a predicted need for help to live independently in the community. This is lower than that reported in the retrospective study of Gagnon et al where 91% of participants needed help to accomplish house‐related tasks independently . These diverging results could be related again to the concept of apathy, where participants are able to perform an activity in a standardized situation, but will not pursue this activity at home because of lack of interest or will.…”
contrasting
confidence: 61%
“…All participants were living either with their parents or in a group home. This is different from the study by Gagnon et al, where 44% of adults were living with a spouse or alone . Eriksson et al found that 62% of their population had a predicted need for help to live independently in the community.…”
mentioning
confidence: 58%
“…This high percentage indicates that adult participants are dependent on others in their daily life. The issue of dependency has been discussed in previous studies, but the additional information yielded by this study suggests that dependency is first and foremost due to weak process skills.…”
Section: Discussionmentioning
confidence: 72%
“…Being able to perform daily activities is key to full participation in society. In a study by Gagnon et al of restrictions to participation in adults with childhood DM1, only 46% of the sample lived independently. Previous studies of the extent to which children and adolescents with congenital and childhood DM1 manage daily activities are based mainly on questionnaires answered by proxies, who evaluated what the individual could do independently but provided no information about how the tasks were performed.…”
mentioning
confidence: 97%
“…The prognosis of DM type 1 is associated with the age of onset (20). Patients with childhood-onset DM typically experience poorer outcomes and have higher mortality rates, whereas patients with adult-onset DM generally exhibit a more favorable prognosis (20). Adult-onset DM type 1, as documented in the present report, is the most prevalent form of the disorder (21).…”
Section: Discussionmentioning
confidence: 99%